Anti-leukaemic and chemotherapy supportive effects of berberis vulgaris l. Fruit crude extract on in vitro and in vivo models - Saedi, Tayebeh Azam (2015)
Cancer is one of the most deadly diseases affecting human, and the second cause of death accounting for about 12.8% worldwide. Among the prominently worldwide cancer-affecting people is leukaemia. The disease is characterized by increasing of immature white blood cells called "blasts", and is estimated to account for about 3% of incident cases for all kind of cancer worldwide. There are different kinds of treatment methods for leukaemia including chemotherapy, which is known to have side effects. However, herbal therapy is considered to have fewer side effects. Hence, the used of Berberis vulgaris crude extract (BVFCE) in treating leukaemia is highlighted. Barberry is an herb derived from Berberidaceae shrub and is known as treat cancer. Total flavonoid and phenolic content (TFC and TPC) and DPPH assay were analyzed by spectrophotometer to determine the antioxidant activity of the Barberry. BVFCE was evaluated for its anti-leukaemic activities against two leukaemic cell lines; Human Promyelocytic (HL-60) and Mouse Myelomonocytic (WEHI-3) versus the normal mouse fibroblast cell (3T3) in both in vitro and in vivo leukaemic model. For the in vitro method, cytotoxic effects of BVFCE were evaluated using MTT assay to determine the IC50 values and compare with non-leukaemic cell line (The 3T3 cell). Observation of the morphological changes in the treated leukaemic cell lines with BVFCE and Doxorubicin (Doxo) was examined using inverted microscope. Moreover, real time PCR was used to amplify mRNA and determine the expression of some specific related genes in leukaemia. Whereas, for the in vivo model, leukaemia was induced in male BALB/c mice using mouse leukaemic cell line (WEHI-3) and treatment was carried out using different concentrations of BVFCE and chemotherapy drug, separately for comparison. After the treatment period (5 weeks), the mice were fasted overnight and sacrificed for biochemical, haematological and histological analyses of their liver, kidney, heart and spleen. All data were analyzed using one-way ANOVA followed by Duncan's multiple post hoc tests. Differences between groups were considered significantly when the p value is less than 0.05. Results showed that BV100 has a higher level of total phenolic and flavonoids contents as well as antioxidant activity as compared with other concentrations (p<0.05). Biochemical assay on alkaline phosphatase (ALP), aspartate aminotransferase (AST), and alanine aminotransferase (ALT) showed significantly lower level of these markers in control and treated groups as compared to cancer group (p<0.05). Leukaemic group showed significantly higher total serum than other groups as well (p<0.05), which indicated the possible beneficial effect of BVFCE treatment on the above named markers. From the haematological finding, the total white blood cell (WBC) count in the cancer group was high. In contrast, the amount of WBC decreased dramatically in mice treated with BVFCE, and doxorubicin compared to the mice group without treatment, which showed a high number of leukaemic cells. Liver, kidney, heart and spleen were stained with haematoxylin and eosin (H&E) and viewed under a light microscope. Spleen and liver weights were significantly low (p< 0.05) in the mice treated groups compared to the untreated group, indicating a significant splenomegaly and hepatomegaly. From the results above, it can be seen that the BVFCE has high anti-leukaemic activity, which might be due to its antioxidant. In conclusion, daily intake of this fruit by groups suffering from leukaemia could suppress or decrease cancer development with no or fewer side effect than the normal chemotherapeutic drug.